Prayer in the three religions: A convergence vision to promote coexistence between - Omar Hassan Saeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Religions Worship to God and religions between (Jewish, Christian and Islamic) they are difference in some of ways but they are same in some other, the wise men of different religions between religions they are sure that religion is the part of nature of human’s they can’t ignore it, this is all heavenly books talk about it. This speech try to show that pray in (Jewish, Christian, and Islamic) are very important part of believe and it’s the top of religions, differences worship of God is not the mean to deleting and separating, the speech have some of the aims: - first praying in (Jewish, Christian and Islamic ) have the same to be close with God. Second, pray focuses to worship to God. Third, each of the religions (kiblah) it’s the same for each of them when they pray. fourth, for doing pray have the same time in morning till night. Fifth, talking about how praying, doing pray and reading heavenly books showing (kiblah) in praying time. The common points are more than with the difference points, at the result (pray) is the way to face with God for prayer. People pray praying to be happy and they ask God to help them